Analiysis of Coastal Ecosystem A Marine Ecotourism at Kokoya Island, Morotai Island District - Kismanto Koroy; Nurafni Nurafni; Fijai Pina (Musamus Fisheries and Marine Journal, 2019)
Coastal ecosystems are dynamic ecosystems that have a rich diversity of habitats on land and in the ocean, as well interacting between one habitat with another. The purpose of this study is to identify the ecological parameters of the coastal ecosystem a marine ecotourism area and determine the suitability class of the Kokoya Island coast as a marine ecotourism area for the coastal tourism category. This research was conducted in January to February 2019. Data collection using primary data with survey methods and direct measurements in the field. The analysis is used to analyze the suitability of the beach ecosystem class on Kokoya Island by using the area suitability matrix for the recreation category of beach tourism. The results showed that at 7 stations in the study location had a Travel Conformance Index in the category of Very Appropriate (S1) and Appropriate (S2). The IKW of each station can be presented; Station 1 IKW. 92.31% (S1), Station 2 IKW. 89.74% (S1), Station 3 IKW. 89.74% (S1), Station 4 IKW. 97.44% (S1), Station 5 IKW. 78.21% (S2), Station 6 IKW. 90.38% (S1), and Station 7 IKW. 97.44% (S1).